Rapid evolution of mouse Y centromere repeat DNA belies recent sequence stability - Pertile, Mark D.; Graham, Alison N.; Choo, K.H. Andy; Kalitsis, Paul (Genome Research, 2009)
The Y centromere sequence of house mouse, Mus musculus, remains unknown despite our otherwise significant knowledge of the genome sequence of this important mammalian model organism. Here, we report the complete molecular characterization of the C57BL/6J chromosome Y centromere, which comprises a highly diverged minor satellite-like sequence (designated Ymin) with higher-order repeat (HOR) sequence organization previously undescribed at mouse centromeres. The Ymin array is ∼90 kb in length and resides within a single BAC clone that provides sequence information spanning an endogenous animal centromere for the first time. By exploiting direct patrilineal inheritance of the Y chromosome, we demonstrate stability of the Y centromere DNA structure spanning at least 175 inbred generations to beyond the time of domestication of the East Asian M.m. molossinus “fancy” mouse through which the Y chromosome was first introduced into the classical inbred laboratory mouse strains. Despite this stability, at least three unequal genetic exchange events have altered Ymin HOR unit length and sequence structure since divergence of the ancestral Mus musculus subspecies around 900,000 yr ago, with major turnover of the HOR arrays driving rapid divergence of sequence and higher-order structure at the mouse Y centromere. A comparative sequence analysis between the human and chimpanzee centromeres indicates a similar rapid divergence of the primate Y centromere. Our data point to a unique DNA sequence and organizational architecture for the mouse Y centromere that has evolved independently of all other mouse centromeres.